Možnost použití chromafinních buněk v léčbě bolesti - Brettschneiderová, Julie; Valenta, Jan; Ševčík, Pavel (Bolest (Praha, Print), 2010)
Chronic pain in oncological patients remains a serious problem. Despite advances in pharmacotherapy, including invasive techniques, nearly 90% of patients in the terminal stages of an oncological disease may suffer from pain. Morphine used to be a gold standard for pain control but there are many adverse effects. Another possibility in pain management is using of the endogenous opioids like dynorphines, enkephaline and ß-endorphine. The main problem limiting their wider usage is a poor penetration to the central nervous system. Chromaffine cells occur in the adrenal medulla and produce high level of the endogenous opioids. Authors prepared review of current status of knowledge in this field. It was found that inserting an autologous graft of adrenal tissue, or heterologous isolated bovine chromaffin cells, into a rat frontal cortex increases antidepressive effect. The autologous and heterologous grafts of chromaffin cells were also inserted intraspinally and decreased pain in animals and patients suffering from pain due to oncological disease. In a clinical experiment two patients had implanted autologous whole-tissue grafts into the subarachnoidal space. In both a successful pain relief was achieved for a one year period. Bovine adrenal glands seem to be a good source of chromaffin cells, because the amount of human adrenal tissue suitable for a potencial transplantation is very limited. To achieve long term production of the chromaffin cell’s products in the central nervous system is one of the main problems as well as finding a suitable form resistant to the immune system. A potential solution to this problem is to place a suspension of the chromaffin cells into a polymer membrane. This can avoid the immune response and the necessity of taking an immunosuppresive therapy. This form of application seems to be safe and potentially usable in humans.
Keywords: nezvladatelná bolest; Transplantation, Autologous; Opioid Peptides; Humans; Chromaffin Cells; analgezie; Chronic Disease; autologní transplantace; krysa rodu Rattus; Pain, Intractable; lidé; modely u zvířat; dřeň nadledvin; chromafinní buňky; Adrenal Medulla; chronická nemoc; transplantace heterologní; klinické zkoušky jako téma; Models, Animal; Rats; Clinical Trials as Topic; opioidní peptidy; Transplantation, Heterologous; Analgesia